2022
DOI: 10.3389/fpubh.2022.976582
|View full text |Cite
|
Sign up to set email alerts
|

Research trends and hotspots of COVID-19 impact on sexual function: A bibliometric analysis based on Web of Science

Abstract: BackgroundThe outbreak of coronavirus disease 2019 (COVID-19) has brought indelible harms to the world and aroused great concern worldwide. This paper aims to analyze the impact of COVID-19 on sexual function using bibliometrics, and summarize research hotspots in this field.MethodsRelevant publications concerning the impact of COVID-19 on sexual function in the Web of Science collection database (WoSCC) between January 1, 2020 and March 12, 2022 were screened and analyzed by bibliometric analysis using the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Xie et al conducted a global analysis using the WoS database on radiotherapy for prostate cancer. They found that the toxicity of genitourinary (GU) in PC therapy cannot be overlooked and is a potential area of research hotspot [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al conducted a global analysis using the WoS database on radiotherapy for prostate cancer. They found that the toxicity of genitourinary (GU) in PC therapy cannot be overlooked and is a potential area of research hotspot [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the research hotspots of PC and ED focus on the mechanism of occurrence, treatment, and management, are continuing to deepen. The United States which stands out among countries contributing to this field ranked first in publications on radiotherapy for prostate cancer worldwide during 2010–2022 [ 16 ]. Memorial Sloan Kettering Cancer Center is not only the most prolific institution, but also holds significant influence globally within this field.…”
Section: Discussionmentioning
confidence: 99%
“…As of January 23, 2023, Since 1969(Pritchard, 1969, bibliometric analysis has been widely used in scientific and application fields (Ellegaard and Wallin, 2015;Huang et al, 2016;Xu et al, 2021). Since 2020, bibliometric analysis has been used (Zhang et al, 2020;Lin et al, 2022;Pang et al, 2022;Xie et al, 2022) to help researchers grasp the knowledge base, hot spots, and trends in the research field of COVID-19. VOSviewer, a powerful bibliometric analysis software developed by van Eck and Waltman in 2010, which offers advanced graphical representation capabilities for mapping knowledge units and their relationships within the research literature (van Eck and Waltman, 2010).…”
Section: Data Source and Analysis Methods Data Sourcementioning
confidence: 99%
“…The data encompassed various aspects such as the annual number of publications, annual citations, publications from different countries and institutions, and categories. The information was imported into Microsoft Excel 2019, Tableau Public, VOSviewer, CiteSpace, and the online bibliometric platform (https://bibliometric.com/) for further examination [16][17][18]. To process the raw data, Tableau Public, a computer science software developed by Stanford University, was employed to create a world map depicting the distribution of publications.…”
Section: Data Analysis and Visualizationmentioning
confidence: 99%